A systematic review of physiological responses to odours with a focus on current methods used in event-related study designs - Loos, Helene; Schreiner, Linda; Karacan, Brid (International Journal of Psychophysiology, 2020)
Objectives: In odour research, there is still a lack of knowledge regarding the detailed understanding of the determinants and the magnitude of an odour's impact on human psychophysiology. Therefore, the present review aims to summarize current evidence on psychophysiological responses to olfactory events, to highlight diversity in research methods, and to provide recommendations for further research. Material and methods: Predefined search items were used for literature research in two databases, focussing on recent investigations of cardiac and electrodermal responses to short (<10 s) olfactory stimulations, combined with self-reports on odour experience, in a healthy population. The selected 27 publications were evaluated with regard to their methods and their findings on psychophysiological correlates of odour stimulation, following a conceptual scheme proposing mediating and moderating factors of physiological responses to odour stimuli. Results: The cardiac and electrodermal activity generally followed a discriminative pattern depending on the perceived pleasantness of an odour. Moreover, the trigeminal aspect of an odour stimulus became evident in electrodermal activity in several studies. Finally, for many of the here addressed potentially mediating and moderating variables, initial findings were obtained in some studies but these await corroboration by future research. With regard to the applied methodology, the reviewed studies were highly diverse, in terms of odour application, study design, and analysis of the time series data. Conclusions: Future research is needed to advance our understanding of, and theoretical concepts beyond, psychophysiological responses to olfactory events, and to achieve experimentally validated methodological guidelines for psychophysiological measurements in olfaction research.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Cardiac activity; Electrodermal activity; Heart rate; Olfaction; Physiological responses; Skin conductance

Correction to: Out of the woods: psychophysiological investigations on wood odors to estimate their suitability as ambient scents (Wood Science and Technology, (2020), 54, 5, (1385-1400), 10.1007/s00226-020-01216-y) - Schreiner, Linda; Karacan, Brid; Blankenagel, Sonja; Packhaeuser, Kai; Freiherr, Jessica; Loos, Helene (Wood Science and Technology, 2021)
The article [Out of the woods: psychophysiological investigations on wood odors to estimate their suitability as ambient scents], written by [Linda Schreiner, Brid Karacan, Sonja Blankenagel, Kai Packhaeuser, Jessica Freiherr and Helene M. Loos], was originally published Online First without Open Access. After publication in volume [54], issue [5], page [1385–1400] the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © [The Author(s)] [2021] and this article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/. The original article has been corrected.
CRIS-Team Scopus Importer:2021-12-17

Identification of odorants in wood of Calocedrus decurrens (Torr.) Florin by aroma extract dilution analysis and two-dimensional gas chromatography-mass spectrometry/olfactometry. - Schreiner, Linda; Loos, Helene; Büttner, Andrea (Analytical and Bioanalytical Chemistry, 2017)

Identification of odorants in wood of Calocedrus decurrens (Torr.) Florin by aroma extract dilution analysis and two-dimensional gas chromatography-mass spectrometry/olfactometry - Schreiner, Linda; Loos, Helene; Büttner, Andrea (Analytical and Bioanalytical Chemistry, 2017)
General emissions of volatile organic compounds from wood are well investigated, but only limited information is available on the odor-active substances contained therein. To close this gap, we aimed at specifically elucidating the odorous constituents of wood from incense cedar [Calocedrus decurrens (Torr.) Florin]; this material is commonly used for the production of a range of products such as pencils and interior accessories. Targeted odorant analysis requires specialized techniques combining modern odorant analytical tools with human-sensory evaluation. Following this concept, the odor profile of the wood sample was first evaluated by human-sensory analyses. Then, the most potent wood odorants were characterized by means of gas chromatography-olfactometry and ranked according to their odor potency via aroma extract dilution analysis. With use of this approach, more than 60 odorous substances were detected, and the 22 most potent odorants were successfully identified by gas chromatography-mass spectrometry/olfactometry and two-dimensional gas chromatography-mass spectrometry/olfactometry. Among the main odorants found were a series of terpenes, several degradation products of fatty acids, and a number of odorants with a phenolic core moiety. Five odorants are reported here for the first time as wood odorants, such as gamma-octalactone and 3-phenylpropanoic acid; thymoquinone was demonstrated for the first time to have a pencil-like odor quality.
Keywords: Aroma extract dilution analysis; Gas chromatography-olfactometry; Incense cedar; 2-Isopropyl-5-methyl-1; 4-benzoquinone; Thymoquinone; Octalactone

Nosy confirmation: reconstitution of the characteristic odor of softwood via quantitative analysis and human sensory evaluation - Schreiner, Linda; Ortner, Eva; Büttner, Andrea (Analytical and Bioanalytical Chemistry, 2020)
The significance of wood odors beyond flavoring effects for barbecues and wine aged in barrels has recently been under discussion. Wood has an immense influence on our physical and mental condition through our palate, such as positive health and mood-stimulating effects. As a result of increased public interest, the key odorants from various natural wood species were recently decoded. To gain profound insights into the contribution of single odorants to the overall scent of distinct wood types, this study compares several softwood species (Scots pine, incense cedar, European larch, Norway spruce, and white fir) by odor profile analysis. Nine odor-active constituents, which were previously detected in those woods, were quantified using stable isotope dilution analysis (SIDA). Odor activity values (OAVs) calculated on the basis of odor thresholds (OTs) determined in cellulose revealed hexanal, octanal, (E)-non-2-enal, p-cresol, vanillin, and thymoquinone as dominant odorants for wood odor. Recombination experiments by mixing the odorants in their naturally occurring concentrations in a cellulose matrix confirmed the successful characterization of the key odorants for Scots pine and incense cedar wood.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Odor activity values; Odor recombination; Thymoquinone; Wood; α-Pinene

Out of the woods: psychophysiological investigations on wood odors to estimate their suitability as ambient scents - Schreiner, Linda; Karacan, Brid; Blankenagel, Sonja; Packhaeuser, Kai; Freiherr, Jessica; Loos, Helene (Wood Science and Technology, 2020)
Wood has been an important raw material for centuries, and humans encounter it in the form of furniture and building materials or in products of daily use. The odors emanating from such wood-based materials can add another facet to their functionality by influencing human well-being and mood. Moreover, wood odors can be used in odor-enhanced environments to foster relaxation and stress recovery. The current study was conducted to assess the subjective evaluation of, and physiological responses to, wood odors and individual wood odor constituents. The subjects smelled the odors of pine needles oil, cedar wood oil, α-pinene, and thymoquinone and evaluated the odor percept and their subjective feelings. Heart rate, finger temperature, and skin conductance were monitored throughout the experiment. The results showed that wood odors were distinct regarding their pleasantness, familiarity, and intensity. All odors enhanced the subjective feelings of happiness and content. Though no odor-specific physiological effects became evident, certain physiological measures correlated with self-reports of happy and relaxed feelings and the intensity ratings of the odors. The present study provides a basis for further studies on the use of wood odors as ambient scents and helps understanding the influence of natural odors on humans.
CRIS-Team Scopus Importer:2020-09-11

Resolving the smell of wood - identification of odour-active compounds in Scots pine (Pinus sylvestris L.) - Schreiner, Linda; Bauer, Patrick; Büttner, Andrea (Scientific Reports, 2018)
Being one of the most common trees in forests, Pinus sylvestris L. is a frequently used raw material for wood products. Its specific odour is, however, mostly unresolved to date. Accordingly, we investigated Scots pine wood samples grown in Germany for their main odorant composition. We employed dedicated odorant analysis techniques such as gas chromatography-olfactometry (GC-O) and aroma extract dilution analysis (AEDA) and successfully detected 44 odour-active compounds; of these, 39 substances were successfully identified by gas chromatography-mass spectrometry/olfactometry (GC-MS/O) and two-dimensional gas chromatography-mass spectrometry/olfactometry (2D-GC-MS/O). Among the main odorants found were (E, E)-nona-2,4-dienal, vanillin, phenylacetic acid, 3-phenylpropanoic acid, d-octalactone and a-pinene, all of them having been detected with high flavour dilution factors during GC-O analyses. The majority of the identified odorants were fatty acid degradation products, plus some terpenoic substances and odorous substances resulting from the degradation of lignin. Although some of the detected substances have previously been reported as constituents of wood, 11 substances are reported here for the first time as odour-active compounds in wood, amongst them heptanoic acid,gamma-octalactone, delta-nonalactone and (E, Z, Z)-trideca-2,4,7-trienal.

Sensory characterization and identification of odorants in birch wood (Betula pendula Roth) - Wang, Qifan; Baum, Adina; Schreiner, Linda; Slavik, Benedikt; Büttner, Andrea; Loos, Helene (Wood Science and Technology, 2024)
As one of the most common tree species, birch wood (Betula pendula Roth) is widely used as a material of furniture and decoration indoors for its many excellent characteristics. Whereas there are some studies on the volatile composition of the essential oil from the leaves of Betula pendula Roth, only limited information is available on the odor-active constituents of birch wood. To close this gap, the odorants of birch wood were investigated by means of instrumental and sensory analyses, including techniques such as gas chromatography-flame ionization detection/olfactometry, high-resolution gas chromatography-mass spectrometry, and heart-cut two-dimensional high-resolution gas chromatography-mass spectrometry/olfactometry. Overall, a total of 20 odorants was (tentatively) identified on the basis of their respective odor qualities and retention indices and mass spectra by comparison with reference compounds. It was shown that birch wood odor is dominated by a series of terpenes, terpenoids and phenyl compounds originating from the degradation of lignin and aldehydes, ketones and acids originating from fatty acid degradation. By a sensory evaluation of the birch wood, the predominant odor attributes were determined to be earthy, pencil-like, corky/mouldy, grassy, fatty, fruity, green tea-like, herb-like, vanilla-like, and vinegar-like.
CRIS-Team Scopus Importer:2024-08-23

Structure-Odor Activity Studies on Derivatives of Aromatic and Oxygenated Monoterpenoids Synthesized by Modifying p-Cymene - Schreiner, Linda; Bauer, Johannes; Ortner, Eva; Büttner, Andrea (Journal of Natural Products, 2020)
Thymoquinone was recently reported as having a unique pencil-like odor and being the impact compound for the cedar-like and cedar wood-based product smell such as pencils. The compounds thymol and carvacrol are structurally related odorants commonly found in plants and foods such as thyme and oregano, also having a significant contribution to their overall aroma. However, a systematic elucidation of the sensory properties in this class of oxygenated, aromatic monoterpenoids has not been carried out. To close this gap and gain new insights into structure-odor relationships leading to pencil-like and woody odors, 19 structurally related derivatives of p-cymene starting from thymol and carvacrol were synthesized and characterized. The compounds had odor thresholds ranging from 2.0 ng/L air to 388.8 ng/L air, being lowest for thymol and carvacrol and highest for thymohydroquinone. The compounds smelled mostly thyme-like, oregano-like, and pencil-like with phenolic, earthy, and medicinal variations in their odor character, which could be successfully linked to structural motifs.
CRIS-Team Scopus Importer:2020-03-31